The Case For Chapbooks: Connecting Your Community With Contemporary Poetry - Rupchan, Juliana (Partnership, 2024)
Collecting contemporary poetry is often a low priority for libraries, but interest in poetry is rising, and many library patrons have the potential to become poetry readers. Building a collection of poetry chapbooks can maximize the impact of a renewed poetry collecting effort because the poetry chapbook is an accessible, high-interest, and often low-cost form that captures the cutting edge of the poetic field. I introduce the poetry chapbook and its creative and social functions and describe various avenues for building a chapbook collection, including acquisition strategies, examples of digital initiatives such as participatory chapbook repository projects, and notes on promoting engagement. The community-building potential and links to higher-level goals such as diverse collecting, local interest, and cultural preservation allow chapbook collections to add unique value to a variety of public, academic, special, and school library contexts.